A problem by أحمد الحلاق

Level pending


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Tom Engelsman
Jan 11, 2021

Convert each term in A A and B B to:

A log 1 / 2 2 k 2 = log 2 2 log 2 1 / 2 2 k = 1 l o g 2 2 2 k = ( 1 2 ) k A \Rightarrow \log_{1/2^{2^k}} 2 = \frac{\log_{2} 2}{\log_{2} 1/2^{2^k}} = \frac{1}{log_{2} 2^{-2^k}} = -(\frac{1}{2})^{k} (i)

B 2 log 2 2 k = 2 log 2 ( 1 / 2 k ) = ( 1 2 ) k B \Rightarrow 2^{-\log_{2} 2^{k}} = 2^{\log_{2} (1/2^k)} = (\frac{1}{2})^k (ii)

such that A + B = Σ k = 1 ( 1 2 ) k ( 1 2 ) k = 0 . A+B = \Sigma_{k=1}^{\infty} (\frac{1}{2})^k - (\frac{1}{2})^k = \boxed{0}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...